Factors Affecting the Increase in Chili Farming Production in Belawa Village, Belawa District, Wajo Regency - Arman Arman; Irmayani Irmayani; Muhammad Hamka; Sitti Rahbiah (Penerbit Goodwood, 2024)
Purpose : This study aims to review the factors influencing chili production in Belawa Village, Belawa District, Wajo Regency, and to examine the impact of production factors (farmer's age, experience, price, seed quality, and land area) on increasing chili production both partially and simultaneously. Methodology/Approach : This research uses a descriptive quantitative approach. Data collection techniques include questionnaires, interviews, observation, and documentation. The data collected were analyzed using multiple linear regression analysis to identify the effect of each variable on chili production. Results/Findings: The results show that: Farmer's age positively affects chili production. Farmer's experience does not positively affect chili production. Price of chili positively affects chili production. Seed quality positively affects chili production. Land area positively affects chili production. Simultaneously, all factors (age, experience, price, seed, and land area) positively affect chili production. Conclusion: This study concludes that factors such as farmer's age, chili price, seed quality, and land area have a positive effect on increasing chili production in Belawa Village. However, farmer's experience does not significantly contribute to increasing chili production. Limitations: This study is limited to Belawa Village, Belawa District, Wajo Regency, and does not consider external factors like climate change and government policies, which may affect the generalizability of the results. Contribution : This research provides new insights into the impact of production factors on chili farming outcomes in Belawa Village and can serve as a reference for the development of agricultural policies that better support chili farmers in increasing their production.